A comparison of postoperative emergence agitation between sevoflurane and thiopental anesthesia induction in pediatric patients - Son, Ji-Seon; Jang, Eunjoo; Oh, Min Wook; Lee, Ji-Hye; Han, Young Jin; Ko, Seonghoon (Korean journal of anesthesiology, 2015)
This study was performed to compare the incidence of emergence agitation (EA) between inhalation and intravenous anesthesia induction in children after sevoflurane anesthesia. In this prospective and double-blind study, 100 children aged 3 to 7 years were enrolled. Subjects were randomly assigned to the sevoflurane (Group S) or thiopental (Group T) anesthesia induction groups. Anesthesia was induced using 8% sevoflurane and 4-6 mg/kg thiopental in Groups S and T, respectively. Anesthesia was maintained with nitrous oxide and sevoflurane. The children were evaluated at 5 and 20 min after arrival in the postanesthesia care unit (PACU) with a four-point agitation scale and the Pediatric Anesthesia Emergence Delirium scale. The incidence of EA and administration of the rescue agent were recorded. The incidence of EA was significantly lower in Group T compared to Group S at 5 min after PACU arrival (3/49 patients, 6% vs. 12/47 patients, 26%, P = 0.019). However, there was no difference between the two groups at 20 min after PACU arrival (23/49 vs. 19/47 patients in Group T vs. Group S, P = 0.425). The overall incidence of EA was 60% (28/47 patients) in Group S and 41% (20/49 patients) in Group T (P = 0.102). The number of children who received propofol as a rescue agent was significantly lower in Group T (Group S: 14/47 vs. Group T: 5/49, P = 0.031). Intravenous anesthesia induction with thiopental reduced the incidence of EA in the early PACU period compared to inhalation induction with sevoflurane in 3- to 7-year-old children undergoing sevoflurane anesthesia.